Commercial Scale Micropropagation of Eucalyptus camaldulensis - Sreedhar, D.; Muralidhar Rao, M.; Ramesh, C.; Lawrence, Leslie (Indian Forester, 1998)
Large scale micropropagation of Ellcalyptlls camaldlliensis clones selected by user agencies was achieved and introduced in various locations to serve as demonstrations for all those concerned with afforestation programmes and tree plantations. Current scenario of forestry segment for private sector participation is discussed.